Síntesis con agrupaciones circulares de dipolos - Suárez Fajardo, Carlos Arturo; Ferrando Bataller, Miguel; Valero Nogueira, Alejandro; Gaona García, Elvis Eduardo (Ingeniería, 2003)
This article describes the synthesis of radiation patterns with circular antenna arrays using the finite dipole in front of a metallic infinite cylinder. The used technique will be that of Fourier, and a method for synthesizing the radiation pattern with antenna array of N dipoles uniformly disposed around a circular ring of radio (b) an in front of a cylinder of radio (a) is proposed. The required excitation currents are determined from a deduced formula in the paper.